Mr. Monk and the new lieutenant - Conrad, Hy (Mr. Monk, 2015)
"An all-new story starring Adrian Monk by Edgar Award-nominated Monk screenwriter and coexecutive producer Hy Conrad. It's compulsive, page-turning fun. Monk and Natalie have finally settled into a new office routine. Now they just need to work things out with their neighbors-a print shop run by hippies whose music leaks through the walls, driving Monk nuts. But the detectives soon have a more serious conflict to deal with: Captain Stottlemeyer's new lieutenant, A.J. Cartledge-a man of limited skills whom Monk finds insufferable. Even the presence of Lieutenant Cartledge won't keep Monk and Natalie from attending the funeral of Judge Oberlin, and it's a good thing. In typical fashion, Monk examines the body in the casket-and finds evidence of poison. The judge was murdered. While there are no traces of the poison at the judge's house, Monk detects that there had been an intruder. The next rainy day, when Captain Stottlemeyer begins to show the same symptoms, Monk deduces that there's a diabolical killer at work, someone who wanted both the judge and the captain dead. Monk and Natalie turn to the captain's ex-lieutenant in Summit, New Jersey for help, but even that might not be enough to solve this crime. With his friend in danger and an enemy close, Monk will have to put his reservations aside to crack the case in time. "--